Resection depth for small colorectal polyps comparing cold snare polypectomy, hot snare polypectomy and underwater endoscopic mucosal resection - Toyosawa, Junki; Yamasaki, Yasushi; Fujimoto, Tsuyoshi; Tanaka, Shouichi; Tanaka, Takehiro; Mitsuhashi, Toshiharu; Okada, Hiroyuki (Endoscopy International Open, 2022)
Background and study aims Small colorectal polyps are removed by various methods, including cold snare polypectomy (CSP), hot snare polypectomy (HSP), and underwater endoscopic mucosal resection (UEMR), but the indications for using these methods are unclear. We retrospectively assessed the efficacy of CSP, HSP, and UEMR for small polyps, focusing on the depth of the resected specimens.Patients and methods Outpatients with non-pedunculated small polyps (endoscopically diagnosed as 6 to 9 mm), resected by two endoscopists between July 2019 and September 2020, were enrolled. We histologically evaluated the specimens resected via CSP, HSP, and UEMR. The main outcome was the containment rate of the muscularis mucosa (MM) and submucosa (SM) tissues.Results Forty polyps resected via CSP (n = 14), HSP (n = 12), or UEMR (n = 14) were enrolled after excluding 13 polyps with resection depths that were difficult to determine. The rates of specimens containing MM and SM tissue differed significantly (57 % and 29 % for CSP, 92 % and 83 % for HSP, and 100 % and 100 % for UEMR, respectively (P = 0.005 for MM and P < 0.001 for SM tissue). Multiple logistic regression analysis showed UEMR was an independent factor relating to the containment of SM tissue. The thickness of SM tissue by CSP, HSP, and UEMR were 52 μm, 623 μm, and 1119 μm, respectively (P < 0.001). The thickness by CSP was significantly less than those by HSP and UEMR (P < 0.001, Bonferroni correction).Conclusions UEMR could be the best method to contain SM tissue without injection. Further studies are needed to evaluate the indication of UEMR for small polyps.